A Socio-Pragmatic Study of Apologies by Moroccan Native Speakers of Arabic - Ismaili Alaoui, Abderrahmane; Benabderrazik, Youssef (International Journal of Language and Literary Studies, 2024)
This study hypothesises that the functions of apology strategies are culture-specific. It is based on the assumption that certain contextual and cultural factors might influence the production and perception of apologies across languages and cultures. The present study investigates apology strategies in Moroccan Arabic, which has not received much attention in cross-cultural pragmatic research. This study examines data from 200 Moroccan Arabic native speakers. It adopts the more structured approach of quantitative research by using a Discourse Completion Task (DCT) to elicit the production of apologies from 10 different social situations between hypothetical interactants. Although this is a pioneering study in its societal context, its main results support earlier findings suggesting the universality of apology strategies; however, the illocutionary forces assigned to these strategies and the identification of new apology strategies reinforce the culture-specific aspect of apologies.